Komunikacja memowa w perspektywie kognitywnej = Memes communication in the perspective of cognitive science - Kufel, Sławomir (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents the current problems of memetics and the need for redefining its basic assumptions. The theses are based in genetics but the essence of memes seems to be that they are reapplicable at their pre-code stage as well. In that sense, memes would code the human culture, including the language. The real challenge today is to actually examine these elements of the memotype that, by analogy with genetics, code the "basic proteins" of our culture.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie